Determinants of Complete Basic Immunization in Children Aged 12-23 Months in Indonesia - Nur Najikhah; Nurjannah Nurjannah; Mudatsir Mudatsir; Said Usman; Irwan Saputra (Budapest International Research and Critics University, 2021)
Complete basic immunization is an effort to prevent disease outbreaks by carrying out complete immunizations with a predetermined schedule and dose, complete basic immunization coverage is one of the five priority health issues in Indonesia, complete basic immunization coverage in Indonesia in 2018 has decreased by 57, 9%, compared to 2013 which was 59.2%. This study identifies the problem of decreasing complete basic immunization coverage based on maternal, child and socio-economic determinants. This study aims to identify the relationship and distribution of complete basic immunization mapping based on maternal age, place of delivery, number of ANC, the child, child's gender, parent's education, parent's occupation and place of residence. Research Methods: The method used is cross-sectional with a total sampling of 6849 respondents. Statistical analysis used was chi square test and logistic regression test was performed using SPSS 24 and thematic maps were generated by ArcGIS. The results of the chi-square test found that there was a relationship between place of delivery, number of ANC, th child, parents' education, parents' occupation, place of residence with complete basic immunization (p≤0.05), had no relationship between maternal age and gender with complete basic immunization (p≥0.05), based on logistic regression test the number of ANC was obtained with (p≤0.05) and based on the mapping of immunization coverage of the third highest category in Central Java, West Nusa Tenggara and East Kalimantan. While the three lowest categories are in the DI Yogyakarta, West Kalimantan and Papua regions. The most dominant factor associated with complete basic immunization is the number of ANC.